The Effect of Centralized-Admission School Lotteries on Between-School Segregation: Evidence from 300 Largest School Districts in the United States - Francisco Lagos; Jason Saltmarsh; Jing Liu (Institute of Labor Economics (IZA), 2025)
This study examines how centralized-admission school lotteries affect between-school racial and ethnic segregation in the largest U.S. public school districts. Using original nationwide panel data and a difference-in-differences design with staggered adoption, the research analyzes effects on school composition, intergroup exposure, and distribution evenness. The findings reveal that centralized-admission lotteries led to increased White student enrollment in district schools and modest improvements in intergroup exposure. Black-White exposure rose by 1.6 percentage points and student of color-White exposure by 1.8 points. However, White students experienced reduced exposure to all racial and ethnic groups, with similar patterns for Black, Asian, and other students of color. While centralized lotteries modestly redistribute students, they do not significantly reduce overall segregation, challenging assumptions about equity-promoting reforms. These results underscore the need for complementary policies including weighted lottery designs, transportation subsidies, and targeted adoption to address the structural roots of school segregation.
Keywords: I24; I28; J15; H75; 330; school segregation; centralized-admission lotteries; school choice; student assignment